Implementation of Motivation and Work Discipline Policy in Order to Improve Teacher Performance at SDN Gading IV Surabaya - Muhammad Jakfar (Lavish Opulent Education, 2025)
This study aims to examine the implementation of work motivation and work discipline policies and their influence on teacher performance at SDN Gading IV Surabaya. Employing a quantitative descriptive research design, data were collected from 25 respondents using a structured questionnaire based on a 5-point Likert scale. The variables were measured using established theoretical frameworks: Maslow and Herzberg for motivation, Hasibuan and Sutrisno for discipline, and Mangkunegara for performance indicators. Descriptive statistical analysis revealed high average scores across all variables: work motivation (4.38), work discipline (4.39), and teacher performance (4.32). The results indicate that teachers at SDN Gading IV demonstrate a strong commitment to professional standards, compliance with institutional policies, and consistent teaching effectiveness. These findings support previous research that links internal behavioral factors with performance outcomes in education. The study concludes that sustained efforts to enhance teacher motivation and discipline can contribute significantly to improving the quality of education. Further research is recommended to explore comparative contexts and integrate additional influencing factors such as leadership and job satisfaction.